Formation And Development of Phraseologisms - Iskhakova Aliya Ildarovna (Zien Journals, 2024)
This article discusses the problems of phraseology in Modern English and Uzbek. It discusses the formation and development of phraseologisms in compared languages
Keywords: phrase; classification; linguistics; phraseological unit